Peningkatan Kesadaran Masyarakat Asing terhadap Risiko Investasi Bodong di Indonesia melalui Edukasi Akuntansi - Rika Nurul Permatasari; Diana Mufidah; Siti Hadawia (Badan Penerbit STIEPARI Press, 2025)
Fraudulent investments pose a real threat to investors, especially foreign investors who lack a thorough understanding of regulations, the financial system, and market conditions in Indonesia. A lack of understanding of basic accounting principles and limited ability to analyze financial statements makes foreigners vulnerable to investment fraud. This community service activity aims to increase foreign literacy and awareness of the risks of fraudulent investments through basic accounting education and the use of legitimate digital financial applications. The activity was conducted online in collaboration with the Malang International Community in March 2025, with participants from various countries currently residing in Malang and the surrounding area. The activity was divided into two main stages. The first stage involved education and counseling on basic accounting principles, including understanding simple financial statements, cash flow analysis, and recognizing indicators of investment fraud. The second stage included training in the use of official digital financial applications registered with the Financial Services Authority (OJK), enabling participants to manage their finances independently and securely. Evaluation results showed that 70% of participants experienced an increased understanding of fraudulent investments, were able to recognize signs of financial fraud, and felt more confident in assessing the legality of investment offers. Basic accounting education has proven effective as a tool to empower foreigners to be more vigilant against rampant illegal investment schemes. This program is expected to become a sustainable model for preventative education, protecting the international community from the risk of losses caused by fraudulent investment practices in Indonesia.